The mTOR inhibitor everolimus attenuates the time course of chronic anti-Thy1 nephritis in the rat - Wittmann, Sandra; Daniel, Christoph; Braun, Andrea; Vogelbacher, Regina; Shimizu, Fuijo; Kawachi, Hiroshi; Hugo, Christian (Nephron Experimental Nephrology, 2008)
Background: The antiproliferative immunosuppressant everolimus adversely affects the acute reversible anti-Thy1 nephritis model. We hypothesized that everolimus treatment started after the acute proliferative phase could even be beneficial in the chronic anti-Thy1 nephritis model in the rat. Methods: Chronic anti-Thy1 nephritis was induced by injection of the monoclonal antibody 1-22-3 in 20 male Sprague-Dawley rats 7 days after uninephrectomy. Two weeks after disease induction, rats were randomly treated with either everolimus or vehicle for 14 weeks. Changes in progression of renal disease were investigated by immunohistochemistry and real-time PCR 16 weeks after disease induction. Results: During chronic anti-Thy1 nephritis, the formation of focal segmental glomerulosclerosis lesions, the degree of interstitial fibrosis as well as the increase in proteinuria over 14 weeks was ameliorated by everolimus treatment. Increased glomerular hypertrophy observed in the vehicle-treated rats was completely prevented in the everolimus-treated nephritic rats. Increased glomerular fibronectin mRNA and protein as well as the renal influx of monocytes/macrophages was significantly reduced in the everolimus group. Everolimus reduced the pro-angiogenic factor vascular endothelial growth factor (VEGF) and VEGF mRNA in glomeruli, while the transforming growth factor-β signaling pathway was not affected. Conclusion: 'Late' start of everolimus treatment demonstrates beneficial effects on the time course of chronic anti-Thy1 nephritis. Copyright © 2008 S. Karger AG.
Created from Fastlane, Scopus look-up
Keywords: Chronic kidney disease; Everolimus; Matrix deposition; mTOR inhibitor; Vascular endothelial growth factor